Efficiency analysis of restaurants operating in the rural ares - Planinc, Tanja (Academica turistica, 2019)
The purpose of this paper is to analyse the efficiency performance of restaurants operating in the rural areas of Slovenia. The sample consisted of 52 independently run rural restaurant facilities. Data were obtained from restaurant managers and restaurant firms' financial reports. Based on a convenience sampling method, only those restaurants whose only source of operating revenues was providing food in a restaurant setting were included in the sample.
Keywords: efficiency; gostilne; gostinstvo; podeželje; restaurant industry; restavracije; Slovenia; Slovenija